Determinants Associated with Premarital Sexual Behavior Among Female Adolescents at Senior High School 13, Tidore Kepulauan City - Wahyuni Wahyuni; Tut Rayani Aksohini Wijayanti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Background: Premarital sexual activity among adolescent girls constitutes a significant reproductive health issue, as it is linked to a higher likelihood of unintended pregnancy, sexually transmitted diseases, and negative psychosocial outcomes. Understanding the determinants of such behavior requires a contextual approach, particularly in Indonesia’s island regions, where social and cultural dynamics may differ. Objective: This research sought to identify determinants related to premarital sexual behavior among female students enrolled at State Senior High School 13 in Tidore Kepulauan City. Methods: A quantitative analytical approach employing a cross-sectional design was implemented. A total of 120 female adolescents were recruited using a simple random sampling technique. Data were obtained through structured self-administered questionnaires and statistically analyzed using the Chi-square test, with a significance threshold of 0.05. Results: The analysis demonstrated that reproductive health knowledge, attitudes toward premarital sexual activity, peer-related influence, and parental involvement showed significant associations with premarital sexual behavior (p < 0.05). Female adolescents who had inadequate knowledge, permissive attitudes, strong peer pressure, and limited parental support exhibited a greater tendency toward engaging in risky premarital sexual practices. Conclusion: Premarital sexual behavior among adolescent girls is influenced by a combination of personal and social determinants. Therefore, integrated promotive and preventive strategies involving both schools and families are essential to mitigate the risk of premarital sexual behavior among female adolescents.